Hubungan antara Perubahan Dispersi QT pada Uji Latih Treadmill dengan Derajat Keparahan Lesi Koroner pada Pasien Terduga Penyakit Jantung Koroner Stabil - Bagus Andi Pramono; Erika Maharani; Bambang Irawan (The Indonesian Heart Association, 2016)
Background: QT Dispersion (QTd) is known as a spatial dispersion indicator during myocardial repolarization, and elongation of QTd is related with ventricular arrhythmia event and sudden cardiac death in ischemic heart disease. The increase of QTd happens in coronary heart disease during myocardial ischemia induced by treadmill test. There is no research linking changes of the QTd (?QTd) on exercise test with the severity of coronary lesions in patients with suspected stable coronary artery disease. The aim of this study was to determine the relationship between QTD changes on exercise test with the severity of coronary lesions in patients with stable coronary artery disease and to determine discriminatory value of QTD changes based on the degree of coronary lesions.Methods: This study was a cross-sectional study in Dr. Sardjito Hospital using data from January 1, 2012. Patients with positive exercise test result, already performed coronary angiography and meet the inclusion and exclusion criteria included in the study. QTd changes during exercise test were measured and Syntax scores were assessed based on the results of coronary angiography. Statistical analysis was performed to determine the relationship between two variables.Results: There were 76 patients with average of 56.64±7.41 years old, with 54 male subjects (71.1%). The most frequent risk factor were hypertension, there were 57 subjects (75%), followed by 32 subjects of dyslipidemia (42.1%), 27 subjects of DM (35.5%), 24 smoker (31.6%), and 2 subjects with family history of CHD (2.6%). Subjects with high Syntax score were 30 subjects (39.5%) and the low Syntax score were 46 subjects (60.5%). In this research, there was positive relationship with medium strength (r=0.531, p<0.001) between ?QTd and Syntax score. Value of QT dispersion changes of 44.78 milliseconds is optimal cut-off point that discriminates between high and low Syntax score.Conclusion: There were positive correlations between changes of QTd dispersion with degree of coronary lesion that was analyzed using Syntax with medium strength.